An Analysis of Total Quality Management (TQM) Implementation on BPJS Patients at Hospital Royal Prima Medan - Muhammad Insan Andika; Ermi Girsang; Sri Lestari Ramadhani Nasution; Gusbakti Gusbakti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The quality of health services is essential in health service organizations in increasing public awareness about health and health services, encouraging every organization to be quality conscious in providing services to service users of health service organizations, Total Quality Management (TQM) is a customer-oriented approach that introduces changes in management that systematic and continuous improvement, which is suitable to meet the quality needs of customers, which is simply a quality product or service if it can satisfy its customers. This study aimed to analyze the implementation of Total Quality Management (TQM) for BPJS inpatients at Royal Prima Hospital Medan. The sample in this study were 133 nurses, data analysis used univariate, bivariate and multivariate analysis.with the level of relationship with the category enough,Respondents' assessment was based on the teamwork variable, the majority of respondents answered satisfactorily, the results showed that there was a relationship between the teamwork variable and the satisfaction of BPJS inpatients at Royal Prima Hospital Medan with a relationship level with a strong category,Respondents' assessment was based on the variable of periodic system improvement, the majority of respondents answered satisfactorily, the results showed that there was a relationship between the variable of irregular system improvement on the satisfaction of BPJS inpatients at Royal Prima Hospital Medan with a relationship level with a strong category.